2020
DOI: 10.1002/jcp.30042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biophysical cues of 3D hydrogels on mesenchymal stem cells differentiation

Abstract: For stem cell research, three‐dimensional (3D) hydrogels are increasingly recognized as more physiological systems than two‐dimensional culture plates due to bidirectional and 3D interaction of stem cells and surrounding matrix. Among various stem cells, mesenchymal stem cells (MSCs) are one of the most widely applied from bench to bedside. In 3D hydrogels, MSCs are allowed to actively remodel the surrounding matrix through proteolytic degradation and cell‐exerted force, which highly resembles in vivo situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Indeed, it has been well documented that MSCs exert traction forces on two dimension substrates to gauge surrounding matrix resistance and that these MSC–substrate interactions involve the integrin receptors of the cells. 110 Bone morphogenetic proteins are extracellular cytokines, which can also be found sequestered in the extracellular matrix, which would be a similar configuration to the immobilized BMP-2 peptide on our hydrogels. It has been shown that BMPs, including BMP-2, interact with transmembrane receptors known as Type I and Type II receptors.…”
Section: Resultsmentioning
confidence: 77%
“…Indeed, it has been well documented that MSCs exert traction forces on two dimension substrates to gauge surrounding matrix resistance and that these MSC–substrate interactions involve the integrin receptors of the cells. 110 Bone morphogenetic proteins are extracellular cytokines, which can also be found sequestered in the extracellular matrix, which would be a similar configuration to the immobilized BMP-2 peptide on our hydrogels. It has been shown that BMPs, including BMP-2, interact with transmembrane receptors known as Type I and Type II receptors.…”
Section: Resultsmentioning
confidence: 77%
“…One explanation for the differences in the mechanosensing capabilities between cells cultured in 2D versus 3D environments is the microtubule cytoskeleton, which is considered the core of the cell structure. In 2D cultures, cells respond to their environment by remodeling the actomyosin cytoskeleton, while the microtubule cytoskeleton is largely insensitive to the underlying substrate . Remodeling of the actomyosin cytoskeleton may be dominated by cell spreading events, while microtubules may help the cell to sense the mechanical environment in the absence of cell spreading .…”
Section: Mechanosensing In 3d Hydrogelsmentioning
confidence: 99%
“…In 2D cultures, cells respond to their environment by remodeling the actomyosin cytoskeleton, while the microtubule cytoskeleton is largely insensitive to the underlying substrate. 271 Remodeling of the actomyosin cytoskeleton may be dominated by cell spreading events, while microtubules may help the cell to sense the mechanical environment in the absence of cell spreading. 272 Studies have reported that microtubule polymerization in 3D hydrogels affects differentiation of MSCs encapsulated in hydrogels that limit cell spreading.…”
Section: Mechanosensory Mechanismsmentioning
confidence: 99%
“…The complex microenvironment provides biomechanical cues that elicit intrinsic signaling cascades in cells. Previous studies have shown that various membrane ligands sense matrix hardness and regulate stem cell fate [ 14 ]. However, the knowledge of complicated intracellular biochemical reactions in the cytoplasm subsequently coordinating to sense matrix stiffness is still unexplored.…”
Section: Introductionmentioning
confidence: 99%